Planning for a Low Carbon Future - World Bank (Washington, DC, 2014)
Developing countries are faced with the dual challenge of reducing poverty while improving management of natural capital and mitigating the emission of greenhouse gases (GHGs) and local pollutants. The challenge is particularly acute for large, rapidly growing economies, such as India, China, and Brazil. In response to this challenge, Energy Sector Management assistance Program (ESMAP) and the World Bank began in 2007 to provide support to countries to develop long term frameworks for reducing GHG emissions in a way that is compatible with economic growth objectives and tied to national and sectoral plans. In total, seven studies were conducted between 2007 and 2010, for the following countries: Brazil, China, India, Indonesia, Mexico, Poland, and South Africa. This report collates the lessons learned from these studies and is intended as a practical guide for government officials, practitioners, and development agencies involved in low carbon development planning. The low carbon studies were tailored to the individual needs of each country involved. In Brazil, India, Indonesia, Mexico, and Poland the studies took the form of an economy-wide analysis of low carbon growth potential, employing a range of data and modeling tools. The governments of China and South Africa conducted their own analyses, but requested the assistance of ESMAP and the World Bank for peer review and to get international expertise on specific focus areas, such as energy efficiency and renewable energy. The combined outputs, and the modeling tools developed as part of the program, represent a significant contribution to international efforts on climate change mitigation and low carbon development.